Pengaruh inovasi produk, harga dan kualitas produk terhadap keputusan pembelian sepeda Motor Honda Beat di Kota Jambi - Indah Suryaning Budi; Ade Octavia; Novita Sari (Jurnal Dinamika Manajemen, 2019)
This study aims to analyze (1) the influence of product innovation variables, price, and product quality both simultaneously and partially on the purchase decision of Honda Beat motorcycles in Jambi City, (2) which variable has the most dominant influence on the purchase decision of Honda motorcycles Beat in Jambi City. The sample used in this research is as many as 100 respondents, where the respondents are the people who own and use Honda Beat motorcycles. Analyzer used is multiple linear regression test. The result of this research shows that (1) simultaneously and partially variable of product innovation and product quality have positive and significant influence to purchasing decision (2) price variable has no significant influence to purchase decision (3) the most dominant variable influence is product innovation.